Functional and phylogenetic diversity of sharks in the Northeastern Pacific. (12th May 2022) - Siders, Zachary A.; Trotta, Lauren B.; Caltabellotta, Fabio P.; Loesser, Katherine B.; Baiser, Benjamin; Ahrens, Robert N. M.
Abstract: Aim: The expansive spatial scale of pelagic communities and the difficulty in acquiring pelagic species' functional traits have stymied an understanding of marine community dynamics. We assembled and analysed a shark trait database and community phylogeny to identify the major axes of trait variation that define shark functional groups. We tested whether membership to biophysical macroecological strata is related to these functional or phylogenetic relationships. Location: Northeastern Pacific, 180–255°E and 0–50°N. Taxon: Sharks (Class: Chondrichthyes, superorder: Selachimorpha). Methods: We built a community phylogeny and collected habitat, reproductive, somatic growth, trophic and dentition traits. We used principal coordinates analyses to identify axes of trait variation and hierarchical clustering to classify functional groups. We tested whether functional or phylogenetic relatedness determined species' membership to strata from five macroecological gradients: latitude, habitat type, thermal, carbon source and bathymetry. Results: We assembled 38 traits from 1225 records from 130 sources, 260 pictographs from seven sources and 631 teeth from 79 jaw specimens. Life history, r versus K selection, was responsible for the biggest division in the functional dendrogram. Vertical habitat preference, growth rates, diet and dental morphology generated further divisions between r ‐ or K ‐selected species. Vertical habitat preference, carbon source and biochemical habitat type were significantly dispersed or clustered on the functional dendrogram or phylogram. Main Conclusions: Habitat and reproductive traits were the most important trait suites driving shark functional diversity. Through ordination and clustering, we were able to associate major axes of trait variation to the membership of shark functional groups. The phylogram approximated well the functional dendrogram's backbone but was a poor substitute for the trait diversity at the tips. Given the long evolutionary history of sharks and coincident expansive trait diversity, merging functional and phylogenetic approaches was necessary to capture the dimensions of shark biodiversity.